Inertia and Movement: The Spatialization of the Native Northland in Jack London's Short Stories. Issue 1 (2nd January 2017) - Wöll, Steffen
Abstract : As an epistemic part of the American West, the Yukon territory or "Northland" is often depicted as a monolithic region: a "last frontier" integrated in a stable national framework attained through the manifest destiny of Anglo-Saxon culture to enlighten a supposedly uncivilized space of cultural and racial otherness. In this article, I argue that Jack London's short stories "An Odyssey of the North" and "The Law of Life" demonstrate the elusiveness of such unequivocal interpretations of the North as a European-American space. In London's diverse and often contradictory oeuvre, one finds not one master narrative transplanted into uncultivated or "exotic" spaces, but in fact manifold variants of both actual and fictional geographies that energize alternative spatial understandings and practices. Although the issues and challenges brought to light in London's fiction have surfaced during the Progressive Era, they still constitute crucial aspects of ongoing processes of coexistence, reconciliation, and conflict among different narratives and voices that claim to represent or know what "makes" the American West. The significance of space for native cultures and the role of Anglo-Saxon "blond beasts" in the Yukon together constitute a variegated discursive pattern, the frictions and interactions of which are at the heart of popular and scholarly discourses that affect not only the American self-concept but also ongoing efforts to understand spatiality as a matter of interdisciplinary significance in the humanities.